Experiences of living with a sexually transmitted disease: an integrative review. Issue 3 (29th November 2017) - Haapa, Toni; Suominen, Tarja; Paavilainen, Eija; Kylmä, Jari
Abstract : Purpose: This integrative review describes experiences related to living with a sexually transmitted disease (STD). Design: The data search was conducted using the CINAHL, MEDLINE (Ovid), PsycINFO and PubMed databases between the years 2000 and 2016. A manual search was also used. The retrieved data consisted of 33 original articles which were analysed using deductive and inductive content analysis. Results: Based on the results, an infected person has a need for information about STDs and experiences emotions such as a loss of purity and control over his/her body. In addition, the ego of the infected person is wounded due to the infection. Concerns about the results of treatments, suffering side effects, and experiences of unprofessional behaviour by nursing staff are related to the treatment of an STD. Having an STD in everyday life means coping with a changing condition, but there are resources that can provide support. The quality of life can also be negatively affected by an STD, and a future with an STD can manifest different hopes and concerns. In relation to other people, an STD has a marked effect, especially concerning sexual relations. The person's sex life can fade away; however, it may remain as an enjoyable experience. The infected person may also adopt safer sexual behaviours or continue with a risk‐taking behaviour. Conclusion: The results of this review can be used in the development of nursing practices, as well as be used in the prevention of STDs.